CALCULATION-EXPERIMENTAL METHOD OF RESEARCH IN A METALLIC CONDUCTOR WITH THE PULSE CURRENT OF ELECTRONIC WAVEPACKAGES AND DE BROGLIE ELECTRONIC HALF-WAVES - Baranov, M. I.; Rudakov, S. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2016)
Purpose. Development of calculation-experimental method for a discovery and study of electronic wavepackages (EWP) and of de Broglie electronic half-waves in a metallic conductor with the pulse axial-flow current of high density. Methodology. Theoretical bases of the electrical engineering, bases of quantum physics, electrophysics bases of technique of high voltage and large pulsecurrents, and also bases of technique of measuring of permanent and variable electric value. Results. On the basis of generalization of results of research of features of the longitudinal wave periodic distributing of negatively charged transmitters of electric current of conductivity in the thin round continuous zincked steel wire offered and approved in the conditions of high-voltage laboratory method for a discovery and direct determination in him of geometrical parameters of «hot» and «cold» longitudinal areas quantized periodic longitudinal EWP and accordingly the mediated determination of values of the quantized lengths formative their de Broglie electronic half-waves. It is shown that results of close quantum mechanical calculations of EWP and quantized lengths λenz/2 of longitudinal de Broglie half-waves for the probed wire long l0 well comport with the results of the executed high temperature experiments on the powerful high-voltage generator of homopolar large pulse current of millisecond duration. Originality. First calculation-experimental a way the important for the theory of electricity fact of existence is set in a round metallic explorer with the impulsive axial-flow current of the quantized coherent de Broglie electronic half-waves, amplitudes of which at the quantum number of n=1,3,9 correspond the middles of «hot» longitudinal areas of EWP. Calculation quantum mechanical correlation of type of λenz/2=l0/n got experimental confirmation, in obedience to which on length of l0 conductor the integer of quantized electronic half-waves is always laid de Broglie. Practical value. The use of the offered method allows to expose electro-technological possibilities of practical application of features sharply not homogeneous periodic wave longitudinal distributing of drifting lone electrons and accordingly by them the conditioned thermal field in round metallic conductors with the electric axial-flow current of high-slay.